Development of Tourism in the Białowieża Forest in 2020-2023 - Jalinik Mikołaj; Łuniewski Stanisław (Studia Ekonomiczne i Regionalne)
The aim of the research undertaken was to present the development of tourism in the Białowieża Forest in the years 2020-2023. This was also the period of the COVID-19 pandemic. The subject of the research were facilities and institutions operating in the Białowieża Forest.